2021
DOI: 10.3389/fneur.2021.625909
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Therapy for Basilar Arterial Trunk Aneurysms

Abstract: Background: Although aneurysms rarely occur in the basilar artery (BA) trunk, the majority of those that do are dissection aneurysms. Currently, the mainstream therapy for BA trunk aneurysms is endovascular therapy (EVT), which mainly includes single coiling or conventional low-metal-coverage stent-assisted EVT, but the efficacy remains to be evaluated.Methods: A retrospective study was performed for the patients who were admitted to our institution for BA trunk aneurysms and underwent EVT. A total of 28 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
3
7
0
Order By: Relevance
“…Angiographic outcome at last follow-up did not significantly differ between the groups; however, incidence of progressive occlusion was significantly higher in the FD group (62.5 vs. 5.7%; p < 0.001). Although the procedure-related complication rate in our study was high, it did not significantly differ between the FD (23.5%) and conventional stent groups (23.3%) and is in line with rates reported in other studies ( 19 , 21 ). The main risk in either group is an ischemic complication.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Angiographic outcome at last follow-up did not significantly differ between the groups; however, incidence of progressive occlusion was significantly higher in the FD group (62.5 vs. 5.7%; p < 0.001). Although the procedure-related complication rate in our study was high, it did not significantly differ between the FD (23.5%) and conventional stent groups (23.3%) and is in line with rates reported in other studies ( 19 , 21 ). The main risk in either group is an ischemic complication.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have reported unsatisfactory outcomes after EVT of BTVBJ aneurysms. Wang et al ( 19 ) reported an 82.1% favorable outcome rate in conjunction with 17.9% mortality. Another study reported a 78.6% satisfactory outcome rate ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only coiling of saccular aneurysms in VBD can result in a good prognosis due to providing the least hemodynamic disturbance. In our previous report, a secular aneurysm on the BA trunk with VBD achieved a good outcome after simple coiling with/without stenting assistance (47). However, for large fusiform and complex aneurysms in VBD, complex EVT, such as FDS deployment, can result in an uncertain and varied prognosis (49).…”
Section: Prognosismentioning
confidence: 95%
“…From nature, most aneurysms associated with VBD are dissecting and can present with saccular or fusiform ( 46 , 47 ). Saccular aneurysms can be treated with the same principle as used for intracranial bifurcation aneurysms ( Figure 7 ).…”
Section: Evt Prospectsmentioning
confidence: 99%
“…For large IFCAs, a conventional self-expandable stent assisted with coiling cannot completely obliterate IFCAs, especially those with branches arising from the aneurysmal wall (77). However, the technique is still useful for target embolization, which targets weak points or ruptured blebs by coiling assisted by conventional stents, especially for acute IFCAs located in the MCA and BA trunk (78,79).…”
Section: Targeted Embolizationmentioning
confidence: 99%